DERMATOGLYPHIC PROFILE AND BASIC PHYSICAL QUALITIES OF JIU-JITSU ATHLETES (Fiep Bulletin - online, 2015)
The present study had as objective to identify dermatoglyphic profiles and the physical qualities that the athletes characterize of high level of jiu-jitsu. As sample, it was used 27 athletes of high level, champions of national, international and pan-american championships. The group was submitted to an evaluation for identification of the dermatoglyphic profile by means of the fingerprints (ID) - according to the Protocol of Cummins and Midlo (1942) - and the physical qualities through neuromuscular tests, push-ups, abdominals and Burpee (FERNANDES FILHO, 2003). The results for the dermatoglyphia were: (A) 0.5 ± 1.17; (L) 6.5 ± 2.44; (W) 3.0 ± 3.42; (D10) 12.7 ±3.42; and (SQTL) 127.3 ± 40.91. The percentages of digital formulas found were: 9.6% AL; 14.3% ALW; 48% LW; 19% WL. For the QFB, it was found the following results: (FB) 52 ± 11.28; (ABD) 48 ± 12.21; (Burpee) 6.5 ± 0.68. According to these results, it is presented a profile of the jiu-jitsu athletes and their QFB in the analyzed aspects, expecting to contribute in the enlargement of this sport.
Keywords: dermatoglyphia; basic physical qualities; jiu-jitsu